Digital Library sebagai Penunjang Pengembangan Perpustakaan Sekolah pada Era Society 5.0 - Soleh, Anjas Rusdiyanto; Arifin, Zainal (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The school library functions as a source of teaching and learning activities for teachers and students at school. This study aims to to describe the development of digital libraries in MTs Negeri 2 Surakarta in the era of society 5.0. It used qualitative research by applying descriptive method. The data source was the SLiMS software used in the library of MTs Negeri 2 State Islamic Junior High School Surakarta and the data was the use of SLiMS related to the management of library collections. Data collection techniques were are note taking and documentation techniques. Data analysis used the interactive model. The result of this research showed that in managing the library, MTs Negeri 2 Surakarta has implemented a digital library, including collection administration, membership services, and circulation services. For the development of society 5.0 era, school-library management involves the librarians in operating SLiMS technology